A dataset of Neotropical liana research focusing on the strategies of control for forest restoration and management practices - da Cunha Vargas, Betânia; Grombone-Guaratini, Maria Tereza; Morellato, Leonor Patrícia Cerdeira (Annals of forest science., 2022)
Key message Forest fragmentation leads to a micro-environmental condition that favors the proliferation of liana, which infest trees, compete with them, and reduce their performance. To report the state of the art of the main actions to manage this structural component of tropical forests, we surveyed the control strategies in the literature in the last 71 years, highlighting research goals, tree-climber interactions, management, restoration, and conservation. Dataset access is at https://doi.org/10.5281/zenodo.6678112 . Associated metadata are available at https://metadata-afs.nancy.inra.fr/geonetwork/srv/fre/catalog.search#/metadata/712ff481-dfa2-4ddb-b4fa-fcbd7c517842 Context Lianas (woody vines) are considered structural parasites of tropical trees because they start their development as terrestrial seedlings but need to reach a tree canopy for higher light availability. The tree-liana coexistence usually can damage tree species, thus removing lianas has been suggested as an alternative to reinforce forest regeneration. Aims The dataset compilation begun during the first author doctoral work and a first dataset on neotropical lianas was published ( https://doi.org/10.5281/zenodo.4050477 ) in 2020. The present dataset ( https://doi.org/10.5281/zenodo.6678112 ) presents an update of the 2020 dataset with additional amend (published articles from 2018 to 2021) and enhanced metadata descriptions. Our aim is providing an updated database extracted from scientific literature compiling information related to the effect of lianas on tree and forest structure and diversity, and to contribute to improve decision making on forest restoration and management. Methods We made a systematic literature review on lianas in the Neotropical region (native or restored) from 1950 to 2021. First, we selected studies on liana management and described each paper according to the following topics: vegetation status, positive (P), and negative (N) effects of lianas on each species, the species in focus, and the suggested management strategy. Results Almost 83% of the studies pointed out tree-climber interactions as negative to trees. Cutting was the management strategy adopted in 92% of the studies. Controlled burning, enrichment, and selective cutting were adopted in only one paper. Rainy and seasonal forests were the vegetation types with more studied sites (20 and 17 respectively). Only one study suggested enhancing forest diversity through direct seeding of lianas. Four studies evaluated the impact of lianas on forest diversity and forest fauna. Conclusion The data collected showed the different impacts of liana management on the diversity and structure of tropical forests. It can endorse environmental control and management practices and evaluate the consequences of these techniques in recovering forests or improving timber production.